Efficacy of Everolimus Low-Dose Treatment for Cardiac Rhabdomyomas in Neonatal Tuberous Sclerosis: Case Report and Literature Review - Luisa Federica Nespoli; Elena Albani; Carla Corti; Luigina Spaccini; Enrico Alfei; Irene Daniele; Gian Vincenzo Zuccotti; Gianluca Lista; Valeria Calcaterra; Savina Mannarino (MDPI AG, 2021)
Background: Cardiac rhabdomyomas (CRs) are the most common cardiac tumors in newborns. Approximately 80-90% of cases are associated with tuberous sclerosis complex (TSC). In selective cases, Everolimus has resulted in a remarkable tumoral regression effect in children with TS. The optimal dosage for neonates is still unknown. Case presentation: We describe the use of Everolimus in a neonate with multiple biventricular CRs, causing subaortic obstruction, in which a low-dose treatment (0.1 mg/die), in an effort to maintain serum trough levels of 3-7 ng/mL, was successfully used off-label, without adverse effects. Conclusions: We showed that a low-dose Everolimus regimen may be an effective and safe treatment for CR regression in TS neonates, when the minimum therapeutic range was maintained.